G-quartet Formation from N9-Benzylguanine Derivatives - Thurlow, Lauren A.; Clay, Khalyd J.; Wene, Taylor P.; Groom, Meg L.; Keyes, Erin S.; Lang, Alexis D.; McCallum, Jeremy E.B. (Letters in Organic Chemistry, 2018)
Achiral N9-benzylguanine derivatives with alkene moieties attached to the benzyl group were synthesized with the intent of targeting a covalently linked unimolecular quadruplex using olefin cross-metathesis. Three N9-(3,5-bis(alkenyloxy)benzyl)-guanine derivatives were synthesized and shown to form stable G-quartet structures in the presence of a central cation. Upon the addition of K+, the guanine derivative, N9-(3,5-Bis(pent-4-en-1-yloxy)benzyl)-guanine, self-assembled into a discrete [G]12-dodecamer quadruplex structure.
Keywords: benzylguanine